2013
DOI: 10.1186/1477-3155-11-42
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of well–dispersed silver nanorods of different aspect ratios and their antimicrobial properties against gram positive and negative bacterial strains

Abstract: In the present contribution, we describe the synthesis of highly dispersed silver nanorods (NRs) of different aspect ratios using a chemical route. The shape and size of the synthesized NRs were characterized by Transmission Electron Microscopy (TEM) and UV-visible spectroscopy. Longitudinal and transverse absorptions bands confirm the rod type structure. The experimentally recorded UV-visible spectra of NRs solutions were fitted by using an expression of the extinction coefficient for rod like nano structures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…Around fifty years ago, it was suggested that the material characteristics could be improved by miniaturization [1,2]. Nanomaterials were used in ancient times with limited ability to probe at the nanoscale and limited understanding of nanotechnology [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Around fifty years ago, it was suggested that the material characteristics could be improved by miniaturization [1,2]. Nanomaterials were used in ancient times with limited ability to probe at the nanoscale and limited understanding of nanotechnology [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…59 However, several authors reported that the antibacterial activity of AgNPs dispersions is more pronounced in case of MSSA and MRSA, as compared to E. coli. 10,20,62,63 Therefore, the bacterial membrane structure is not the only factor that affects the antibacterial activity of nanoparticles, but also the sources of the bacterial strains.…”
mentioning
confidence: 99%
“…In order to synthesize AgNPs, two stock solutions of 2 Â 10 À3 M NaBH 4 and 1 Â 10 À3 M AgNO 3 were prepared separately in ice cold water and kept them in ice after preparation. The detailed synthesis of AgNPs has been reported in our recent studies [30,31]. The mean size of the AgNPs is determined with the help of UV-Vis absorption spectra and TEM measurements, as shown in Fig .…”
Section: Methodsmentioning
confidence: 99%